2018
DOI: 10.3390/nu10081098
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Nutrition and Physical Activity Cancer Prevention Guidelines and Development of Colorectal Adenoma

Abstract: Adherence to the American Cancer Society’s (ACS) Nutrition and Physical Activity Cancer Prevention Guidelines is associated with reductions in overall cancer incidence and mortality, including site-specific cancers such as colorectal cancer. We examined the relationship between baseline adherence to the ACS guidelines and (1) baseline adenoma characteristics and (2) odds of recurrent colorectal adenomas over 3 years of follow-up. Cross-sectional and prospective analyses with a pooled sample of participants fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…The NCCN Guidelines Insights do not represent the full NCCN Guidelines; further, the National Comprehensive Cancer Network ® (NCCN ® ) makes no representations or warranties of any kind regarding their content, use, or application of the NCCN Guidelines and NCCN Guidelines Insights and disclaims any responsibility for their application or use in any way. 1 Duke Cancer Institute; 2 Vanderbilt-Ingram Cancer Center; 3 Yale Cancer Center/Smilow Cancer Hospital; 4 University of Wisconsin Carbone Cancer Center; 5 UC San Diego Moores Cancer Center; 6 Case Comprehensive Cancer Center/University Hospitals Seidman Cancer Center and Cleveland Clinic Taussig Cancer Institute; 7 Siteman Cancer Center at Barnes-Jewish Hospital and Washington University School of Medicine; 8 Moffitt Cancer Center; 9 The Sidney Kimmel Comprehensive Cancer Center at Johns Hopkins; 10 Roswell Park Comprehensive Cancer Center; 11 Mayo Clinic Cancer Center; 12 Robert H. Lurie Comprehensive Cancer Center of Northwestern University; 13 Fred Hutchinson Cancer Center/Seattle Cancer Care Alliance; 14 Fox Chase Cancer Center; 15 Huntsman Cancer Institute at the University of Utah; 16 City of Hope National Medical Center; 17 Fred & Pamela Buffett Cancer Center; 18 University of Michigan Rogel Cancer Center; 19 Memorial Sloan Kettering Cancer Center; 20 UCLA Jonsson Comprehensive Cancer Center; 21 Dana-Farber/Brigham and Women's Cancer Center | Massachusetts General Hospital Cancer Center; 22 Abramson Cancer Center at the University of Pennsylvania; 23 University of Colorado Cancer Center; 24 O'Neal Comprehensive Cancer Center at UAB; 25 The Ohio State University Comprehensive Cancer Center -James Cancer Hospital and Solove Research Institute; 26 UCSF Helen Diller Family Comprehensive Cancer Center; and 27 National Comprehensive Cancer Network.…”
Section: Please Notementioning
confidence: 99%
See 1 more Smart Citation
“…The NCCN Guidelines Insights do not represent the full NCCN Guidelines; further, the National Comprehensive Cancer Network ® (NCCN ® ) makes no representations or warranties of any kind regarding their content, use, or application of the NCCN Guidelines and NCCN Guidelines Insights and disclaims any responsibility for their application or use in any way. 1 Duke Cancer Institute; 2 Vanderbilt-Ingram Cancer Center; 3 Yale Cancer Center/Smilow Cancer Hospital; 4 University of Wisconsin Carbone Cancer Center; 5 UC San Diego Moores Cancer Center; 6 Case Comprehensive Cancer Center/University Hospitals Seidman Cancer Center and Cleveland Clinic Taussig Cancer Institute; 7 Siteman Cancer Center at Barnes-Jewish Hospital and Washington University School of Medicine; 8 Moffitt Cancer Center; 9 The Sidney Kimmel Comprehensive Cancer Center at Johns Hopkins; 10 Roswell Park Comprehensive Cancer Center; 11 Mayo Clinic Cancer Center; 12 Robert H. Lurie Comprehensive Cancer Center of Northwestern University; 13 Fred Hutchinson Cancer Center/Seattle Cancer Care Alliance; 14 Fox Chase Cancer Center; 15 Huntsman Cancer Institute at the University of Utah; 16 City of Hope National Medical Center; 17 Fred & Pamela Buffett Cancer Center; 18 University of Michigan Rogel Cancer Center; 19 Memorial Sloan Kettering Cancer Center; 20 UCLA Jonsson Comprehensive Cancer Center; 21 Dana-Farber/Brigham and Women's Cancer Center | Massachusetts General Hospital Cancer Center; 22 Abramson Cancer Center at the University of Pennsylvania; 23 University of Colorado Cancer Center; 24 O'Neal Comprehensive Cancer Center at UAB; 25 The Ohio State University Comprehensive Cancer Center -James Cancer Hospital and Solove Research Institute; 26 UCSF Helen Diller Family Comprehensive Cancer Center; and 27 National Comprehensive Cancer Network.…”
Section: Please Notementioning
confidence: 99%
“…16 Other analyses have shown that adherence to guidelines promoting physical activity and a healthy diet are associated with reductions in the incidence of CRC. 17,18 Initiating physical activity during adolescence also appears to lower the risk of developing colorectal adenomas later in life. 19 In regard to diet and nutrition, the CUP report recommends obtaining nutrients from natural food sources over solely from dietary supplements.…”
Section: Physical Activity and Dietmentioning
confidence: 99%
“…Walnuts (genus Juglans) have been shown to suppress colon cancer in mice models through the decreased expression of miR-1903, miR-467c, and miR-3068, as well as the increased expression of miR-297a in athymic nude mice injected subcutaneously with HT-29 CRC cells [520] (Figure 9d) [531-533] have proven efficacy in this situation. Also, Algae derived astaxanthin [534][535][536][537][538][539][540], fucoxanthin [541][542][543][544][545], lutein and zeaxanthin [546][547][548][549], polyphenols [550][551][552][553][554] shown individual excellence (Figure 9). Propolis is a well-known health supplement that is extremely popular in Australia and New Zealand.…”
Section: Mundulea Sericeamentioning
confidence: 99%
“… 16 - 18 Adherence to dietary and PA recommendations, such as those outlined by the American Cancer Society (ACS), World Cancer Research Fund, and American Institute for Cancer Research (AICR) is associated with reduced odds of having 3 or more adenomas colorectal adenomas. 19 - 21 …”
Section: Introductionmentioning
confidence: 99%